2020
DOI: 10.1007/s00167-020-06165-4
|View full text |Cite
|
Sign up to set email alerts
|

Higher satisfaction after total knee arthroplasty using restricted inverse kinematic alignment compared to adjusted mechanical alignment

Abstract: Purpose Various alignment philosophies for total knee arthroplasty (TKA) have been described, all striving to achieve excellent long-term implant survival and good functional outcomes. In recent years, in search of higher functionality and patient satisfaction, a shift towards more tailored and patient-specific alignment is seen. The purpose of this study was to describe a restricted 'inverse kinematic alignment' (iKA) technique, and to compare clinical outcomes of patients that underwent robotic-assisted TKA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
101
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 32 publications
5
101
0
1
Order By: Relevance
“…In our study, we found similar tibial resection angle in the aMA and MA groups. However, the overall coronal limb alignment averaged 1.11° more varus/valgus and femoral component was placed in 2.29° more varus/valgus in the aMA group, which is consistent with the ndings of Winnock et al, who adjusted femoral component to preserve mild constitutional deformity with the aMA technique [28]. These ndings also match the stated concept of kinematic alignment technique to reverse the alignment of the pre-arthritis native knee [33].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our study, we found similar tibial resection angle in the aMA and MA groups. However, the overall coronal limb alignment averaged 1.11° more varus/valgus and femoral component was placed in 2.29° more varus/valgus in the aMA group, which is consistent with the ndings of Winnock et al, who adjusted femoral component to preserve mild constitutional deformity with the aMA technique [28]. These ndings also match the stated concept of kinematic alignment technique to reverse the alignment of the pre-arthritis native knee [33].…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, aMA technique is considered as an extension of the conventional MA technique in TKA, aiming to correct the coronal lower limb deformity within a maximum of 3° varus or valgus by tuned the position of femoral component, without performed soft tissue releases as much as possible. aMA-TKA was reported to provide good clinical outcomes for varus and valgus knees [28]. However, as far as we are aware, no comparable clinical study between aMA and MA technique in TKA has been previously performed, which is possibly due to the limited choices of alignment technique under conventional instruments.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, these systems allow for accuracy in implant positioning and limb alignment and can facilitate the alignment reflection. Some authors have even described an adaptation of the kinematic alignment with the robotic-assisted system [100,101].…”
Section: Tka Resultsmentioning
confidence: 99%
“…Winnock de Grave et al described this new concept and technique with a robotic-assisted system [ 34 ]. The tibial implant is positioned first with resection of equal amounts of bone lateral and medial on the tibia, after correcting for bone wear.…”
Section: Inverse Kinematic Alignmentmentioning
confidence: 99%
“…Only Winnock de Grave et al have reported the outcomes of the inverse KA. They found no significant difference in clinical results at 12 months between inverse KA and adjusted MA [ 34 ]. They reported a higher rate of satisfaction and significant improvement in postoperative OKS for restricted inverse KA, compared to adjusted MA.…”
Section: Inverse Kinematic Alignmentmentioning
confidence: 99%